The use of echocardiography in type 1 diabetes - Weber, Thaís Rossoni; da Silva, Roberto Léo; Cossul, Sandra; Alves, Marco Stephan Lofrano; Lee, Simone Van der Sander; Marques, Jefferson Luiz Brum (Revista portuguesa de cardiologia (English ed.), 2021)
Type 1 diabetes (T1D) is a chronic disease with peak incidence in adolescence; it has a major impact on morbidity and mortality, especially cardiovascular. Diabetic cardiomyopathy is characterized by structural and functional lesions in the absence of other diseases and is involved in the progression to heart failure. Echocardiography has led to the identification of early cardiac lesions, despite controversial results in the literature in patients with T1D. The objective of this study is to assess cardiac changes in individuals with TD1 compared to the control group using conventional two-dimensional Doppler and advanced speckle tracking echocardiography. This is a case-control study with 40 asymptomatic, normotensive T1D patients aged 20 to 50 years and 40 healthy subjects. Two-dimensional echocardiography was performed to measure myocardial thickness and cardiac chambers. Tissue Doppler echocardiography was used for diastolic analysis and speckle tracking echocardiography to quantify ventricular systolic function. The mean age was 33 years in both groups, with an average T1D duration of 18 years; 20% of patients with T1D had diabetic retinopathy; 12.5% kidney injury; and 10% peripheral neuropathy. There were differences in the left ventricular diastolic function parameters (lateral E', middle E' and S/D ratio) and right ventricle (tricuspid E and tricuspid E'/A' ratio). The mean value of the global longitudinal strain was -21.7% (+- 2.3) in the T1D group and -21.0% (+-2.0) in the control group (p=0.21). Echocardiography revealed a reduction in indices of diastolic function in T1D compared to the control group, which may be the initial cardiac lesion in diabetes.